The Competence of Court in Corruption Investigation - Faris Almer Romadhona; Enrico Pinantun Hamonangan Hutasoit; Dio Aliefs Taufan; Farisy Lazwardi Robbani (Budapest International Research and Critics University, 2022)
Arbitrary empowerment of public officials or management of the state is a logical consequence of the concept of the welfare state. This opens the door for officials to commit corrupt acts. According to the provisions of the administrative law, the abuse of power by civil servants is not a crime but only the fault of the management agency. However, with the enactment of the Government Administration Act, judges in the courts dealing with corruption crimes have the power to judge whether there is an element of abuse of position. Better laws and no negative effects or more problems. Reviews and updates need to be made to achieve maximum results and satisfy all parties.